Two new enigmatic species of the genus Merodon Meigen (Diptera: Syrphidae) from the north-eastern Middle East - Vujić, Ante; Radenković, Snežana; Likov, Laura; Andrić, Andrijana; Gilasian, Ebrahim; Barkalov, Anatolij (Zootaxa, 2019)
Two new remarkable species of the genus Merodon Meigen (Diptera: Syrphidae) are described from biodiversity hotspots in the Middle East: Merodon eumerusi Vujić, Radenković et Likov sp. n. and Merodon mixtum Vujić, Radenković et Likov sp. n. Although M. eumerusi, from the Mountains of Central Asia, belongs clearly to the lineage of M. avidus-nigritarsis, it possesses some unique features within the genus that are also present in other Merodontini genera. M. mixtum, from the Irano-Anatolian mountains, has typical characters of different species groups within the M. albifrons lineage. Here, we discuss the unusual apomorphic characters of these newly discovered taxa and highlight the need for further analyses to ascertain the phylogenetic relationships within the tribe Merodontini and the genus Merodon.